PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI PERMAINAN ULAR TANGGADHITA PARANITA NINGTYAS - NINGTYAS, DHITA PARANITA (JPUD - Jurnal Pendidikan Usia Dini, 2014)
The aim of this research is to improving the beginning reading abilty in group B PAUD Permata Bunda Blitar. The learning process through Ular Tangga consist how to know the alfabet, words, simple sentences and the meaning of words or sentences.The research used action research method according to Kemmis and Taggart made throught two cycle consisting of 16 sessions. The cycle consist of planning, action (acting), observation (observing), and reflection (reflecting). Before the beginning observation as a comparison after the action observation is done, so that the percentage target of the learning achievement could be measured. With Ular tangga game, its prove if learn reading can with games and it is can make easy learn reading. The data was collected by the research instrument in the form of the test result to early reading ability pre-cycle and the results to early reading ability after cycle I and cycle II. The end result of this research shows that the reading throught Ular Tangga game could increase early reading ability of grade B Kindergarten student who evidenced by the acquisition of clasical scores early reading pre-action reaches 38,88%. After the first cycle increase the scores reaches 79,67% and the second cycle is optaineded satisfactory clasical scores reaches 90%. Ular tangga game it should be alternatif to teach reading for the children. Keywords: Reading Ability, Early Childhod, Ular Tangga Game Abstrak: Tujuan penelitian untuk meningkatkan kemampuan membaca permulaan anak TK B diPAUD Permata Bunda Blitar. Kemampuan membaca permulaan meliputi kemampuan untuk mengenal huruf, suku kata, kata, membaca kalimat dan memaknai kata dan kalimat. Penelitian ini menggunakan metode penelitian tindakan menurut Kemmis dan Taggart dengan dua siklus yang terdiri dari 16 pertemuan. Siklus terdiri dari perencanaan (planning), tindakan (acting), pengamatan (observasi), dan mencerminkan (refleksi). Penelitian pra tindakan untuk mengetahui hasil presentase kemampuan awal. Dengan permainan ular tangga, dapat membuat belajar membaca menjadi lebih mudah. Hasil penelitian menjelaskan bahwa kemampuan membaca anak kelompok B meningkat, yang dilihat dari kenaikan skor klasikal dari kegiatan pra tindakan 38,88%. Setelah diadakan siklus I menjadi meningkat 79,67%, dan siklus II meningkat menjadi 90%. Permainan ular tangga dapat mejadi alternatif mengajarkan membaca untuk anak. Kata kunci: Kemampuan Membaca, Anak Usia Dini, Permainan Ular Tangga